2012
DOI: 10.1371/journal.pntd.0001722
|View full text |Cite
|
Sign up to set email alerts
|

Unequivocal Identification of Subpopulations in Putative Multiclonal Trypanosoma cruzi Strains by FACs Single Cell Sorting and Genotyping

Abstract: Trypanosoma cruzi, the etiological agent of Chagas disease, is a polymorphic species. Evidence suggests that the majority of the T. cruzi populations isolated from afflicted humans, reservoir animals, or vectors are multiclonal. However, the extent and the complexity of multiclonality remain to be established, since aneuploidy cannot be excluded and current conventional cloning methods cannot identify all the representative clones in an infection. To answer this question, we adapted a methodology originally de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…A similar initiative was proposed to develop a Multilocus Sequence Typing (MLST) scheme based on the analysis of a panel of four molecular targets: Met-III, RB19, TcGPXII, and DHFR-TS; however, the development of this process requires both bioinformatic analysis and sequencing steps [9]. Recently, the analysis of the polymorphisms of the 24sα rDNA gene, the subunit II of the cytochrome oxidase, and four microsatellite loci has been shown to be an alternative method [10]. This technique is highly efficient but requires multiple amplification steps that can lead to an increased risk of contamination.…”
Section: Resultsmentioning
confidence: 99%
“…A similar initiative was proposed to develop a Multilocus Sequence Typing (MLST) scheme based on the analysis of a panel of four molecular targets: Met-III, RB19, TcGPXII, and DHFR-TS; however, the development of this process requires both bioinformatic analysis and sequencing steps [9]. Recently, the analysis of the polymorphisms of the 24sα rDNA gene, the subunit II of the cytochrome oxidase, and four microsatellite loci has been shown to be an alternative method [10]. This technique is highly efficient but requires multiple amplification steps that can lead to an increased risk of contamination.…”
Section: Resultsmentioning
confidence: 99%
“…This premise emerges in the light of the absence of triple peaks among the loci studies or heterozygosis status; only locus TcATT14 showed heterozygosis and the rest of loci employed were homozygous, this could be explained by a low resolution power displayed by the microsatellite markers employed since parasite DNA yield was high (Table 2). Additionally, the multi-copy arrangement that SL-IR displays and the presence of null alleles and/or aneuploidy could explain these premises but further testing is required [44].…”
Section: Discussionmentioning
confidence: 99%
“…Such coupled genotyping would enhance resolution of parasite-vector genetic co-structure and thus, for example, help quantify rates of parasite transmission from domiciliating vectors or determine whether parasite gene flow proxies for (or improves understanding of) dispersal patterns in more slowly evolving vectors or hosts. It would also be interesting to test in how far deep-sequenced GLST libraries could help in detecting (and reconstructing distinct MLGs from) multiclonal T. cruzi infections without the use of cloning tools 101 , e.g., using bioinformatic strategies developed for malaria research 102105 . Multiclonality has important implications for public health 106,107 but its potential prevalence in T. cruzi vectors and hosts 108,101,109 is difficult to describe from cultured cells 108,110 .…”
Section: Discussionmentioning
confidence: 99%